2015
DOI: 10.4238/2015.february.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Association between macrophage migration inhibitory factor rs1007888 and GDM

C Li2,
et al.

Abstract: ABSTRACT. We investigated the association between macrophage migration inhibitory factor (MIF) rs1007888 single-nucleotide polymorphisms and the genetic susceptibility to gestational diabetes mellitus (GDM). A total of 240 GDM pregnant women (GDM group) and 330 healthy pregnant women (control group) were included in the study. Differences in the MIF rs1007888 genotype and allele frequencies and differences between fasting blood glucose, fasting insulin, homeostatic model assessment (HOMA)-insulin resistance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The macrophage migration inhibitory factor (MIF), is a pro-inflammatory cytokine secreted by T-lymphocytes in response to delayed-type hypersensitivity, which exerts an inhibitory effect on macrophage migration. The rs755622 polymorphism of this gene (MIF-173G/C) is associated with higher GDM risk (OR: 1.59) ( Li et al, 2016 ), and the rs1007888 polymorphism is related to high levels of blood glucose and insulin ( Zhan et al, 2015 ).…”
Section: Genetic Factors Associated With Gestational Diabetes Mellitu...mentioning
confidence: 99%
“…The macrophage migration inhibitory factor (MIF), is a pro-inflammatory cytokine secreted by T-lymphocytes in response to delayed-type hypersensitivity, which exerts an inhibitory effect on macrophage migration. The rs755622 polymorphism of this gene (MIF-173G/C) is associated with higher GDM risk (OR: 1.59) ( Li et al, 2016 ), and the rs1007888 polymorphism is related to high levels of blood glucose and insulin ( Zhan et al, 2015 ).…”
Section: Genetic Factors Associated With Gestational Diabetes Mellitu...mentioning
confidence: 99%
“…The macrophage migration inhibitory factor (MIF) gene is positioned at 22q11.23 [62]. Although MIF molecules are not considered to belong to the cytokine family [63], most participate in the critical regulatory functions of macrophage and lymphocyte activation in innate and adaptive immune responses, and the MIF gene has been identified to be a novel candidate gene for T2DM [64]. When MIF levels are attenuated, glucose pathways are improved due to reduced peripheral insulin resistance and the regulatory effects of glucocorticoids [62,65].…”
Section: Genes Involved In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%
“…Further, Yilmaz et al found that serum insulin levels and MIF concentrations in Caucasian women with GDM in Turkey were significantly higher than in healthy control women, suggesting that MIF may play a role in the development of GDM [65]. Studies have shown that fasting blood glucose and insulin levels and insulin resistance in pregnant women with the GG genotype MIF rs1007888 were significantly higher than in pregnant women with other genotypes [63]. The number of rs755622 C allele carriers in GDM women was also significantly higher than in the normal control group, suggesting that this allele may be a risk factor for GDM [64] Aslani et al also found a high frequency of the rs1007888 GG genotype and a significant association with preconception obesity in Indian women with GDM [62].…”
Section: Genes Involved In Glucose Metabolism and Insulin Resistancementioning
confidence: 99%
“…Another MØ secretory signal, a pro-inflammatory cytokine known as MØ migration inhibitory factor (MIF) which stimulates TH1 cells, induces IL-17 release, and increases TLR-4 expression on MØ is used for GDM prediction ( Figure 2C ) ( Yilmaz et al, 2012 ). Moreover, GDM susceptibility has also been determined by specific genotypes associated with MIF ( Aslani et al, 2011 ; Zhan et al, 2015 ). Decreased Treg numbers are associated with GDM prognosis, as shown in multiple studies where subsets of suppressive Tregs, CD4 + CD127LOW+/CD25 + Tregs and CD45RA Tregs were evaluated during GDM pregnancies and represented a decline of anti-inflammatory function of Tregs as early as in the first trimester of GDM pregnancy ( Schober et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%